KARAWITAN TARI TOPENG SEKARTAJI TUNGGAL - Rini Rahayu (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2018)
AbstractTopeng Sekartaji Tunggal is dance which is inspired from the inner turmoil of the Dewi Sekartaji, a beloved daughter of protagonist Panji Asmarabangun commonly contained in narratives of Serat Panji. This research aims to know karawitan dance musical idea